(3OjhGf GdWGdbGfjs - (3ehSi GdWGdbGfj GdfLaj,J (B1296 (3g` s
(3ChdgG (B:s
(3Mqj GdYPjH hQGeI hVHGAgG hGfTb YHjQ Gde jLR CQLGAgG s
(3BNQgG (B:s
(3JQGg jhe GdHPd ZjKkG eeQYG haj GddbG JdbGg djKG CQhYG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B145 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(1737) s
Keywords: (3GdCOHs